Analisis Maqashid Al-Syari’ah dalam Pemikiran Islam Imam Al-Syatibi - Risma Hermawati Apriliani; Salsabila Putri Virgiawan; Lina Marlina (Journal of Islamic Economics and Finance, 2025)
A Economic inequality is a global issue that has an impact on social stability and people's welfare. To overcome this problem, government intervention is needed through fiscal policy. From the perspective of sharia maqashid, the main goal of economic policy is to maintain the benefit of the ummah through the fulfillment of basic needs, equitable distribution of wealth, and protection of the rights of individuals and communities. One of the scholars who made a great contribution to the thinking of sharia maqashid in economics was Imam Al-Syatibi. Imam Al-Syatibi, a prominent s cholar of ushul fiqh in the 14th century, is known for his contribution in developing the concept of maqasid sharia, which is the goals of Islamic sharia that focus on the benefit of mankind. Imam Al-Shatibi's thought is not only limited to the realm of Islamic law, but also provides a deep perspective in the field of Islamic economics. This research aims to explore Imam Al-Syatibi's economic thinking, especially how the principles of maqasid sharia are applied in economic activities to achieve welfare and social justice. Through a descriptive qualitative approach, this research analyzes the economic concepts proposed by Imam Al-Syatibi and their relevance in the context of modern economics. The results of the study show that Imam Al-Shatibi's thinking emphasizes the importance of a balance between individual and societal needs, as well as the need for fair economic regulation in accordance with sharia principles.